UJI DAYA HAMBAT EKSTRAK ETANOL HERBA KROKOT (Portulaca oleracea L.) TERHADAP BAKTERI Staphylococcus epidermidis - Annisa Diyan Meitasari; Rosa Juwita Hesturini; Infika Indriana (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2021)
Purslane is a plant that is empirically used in medicine, one of the benefits is that can inhibit the growth of bacteria. The study aimed to identify the obstruent extract ethanol herbaceous purslane (Portulaca oleracea L.) against Staphylococcus bacteria epidermidis. Extraction of herbaceous purslane using maceration method with 96% ethanol solvent for five day. Bacterial inhibition test was carried out using the disc diffusion method with variantions concentration extract of purslane herbaceous 25%, 50%, and 75%. The Results of the inhibition test of purslane herbaceous ethanol showed that purslane herbaceous extract could inhibit Staphylococcus epidermidis bacteria. At a concentration of 25% (10,0), 50% (11,0), and 75% (11,5) with positive control chloramfenicol (22,2). From the results of the inhibition test of the both extract ethanol herbaceous purslane, the concentration was resistent to Staphylococcus epidermidis bacteria.